2012
DOI: 10.1111/j.1365-277x.2012.01245.x
|View full text |Cite
|
Sign up to set email alerts
|

Portion size estimation aids for Asian foods

Abstract: Accuracy and precision of a combination PSEA is convincing, enabling inclusion into an Asian food atlas for dietary assessment and intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
47
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(47 citation statements)
references
References 27 publications
0
47
0
Order By: Relevance
“…Combined PSEEs of all 4 aids: 68.3% (n = 3180). Diagrams produced fewest over-/underestimates but were not good for all amorphous food (photos better)Thoradeniya et al (2012) 56 Sri Lanka1029 adults aged ≥30 y from rural areasHousehold utensil units for 3-d EFR. Portions based on government guidelines 67 Case–control study examining the association between intake of β-carotene from fruit and vegetables and risk of oral cancerNo information reported on the accuracy or validity of estimated portions in this population.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Combined PSEEs of all 4 aids: 68.3% (n = 3180). Diagrams produced fewest over-/underestimates but were not good for all amorphous food (photos better)Thoradeniya et al (2012) 56 Sri Lanka1029 adults aged ≥30 y from rural areasHousehold utensil units for 3-d EFR. Portions based on government guidelines 67 Case–control study examining the association between intake of β-carotene from fruit and vegetables and risk of oral cancerNo information reported on the accuracy or validity of estimated portions in this population.…”
Section: Resultsmentioning
confidence: 99%
“…Impact of textureLanerolle et al (2013) 11

Sri Lanka

High-school children aged 10–16 y

Stand-alone and combined PSEEs (small and life-size photos, life-size line diagrams, and household spoons in 3 sizes). Portion sizes based on government 67 and other schemes 70 , 71 , 56 Validation vs actual weight (as assessed by 80 teenagers) for 4 PSEAs. Portion sizes derived from consumption studies.
…”
Section: Resultsmentioning
confidence: 99%
“…One study tested a photographic atlas on eighty children in Sri Lanka (22) . The authors reported that 57 % of portion size estimations using life-size photographs were estimated correctly (i.e.…”
mentioning
confidence: 99%
“…Although a number of food atlases for different countries are 59 available (Harrington et al, 2001;KISR, 2010;Nelson et al, 1997;60 Thoradeniya et al, 2012;Tueni et al, 2012), it is recommended that 61 photographic food atlases should be country and age specific 62 (Andersen et al, 2011;Foster et al, 2008;Thoradeniya et al, 2012). 63…”
mentioning
confidence: 99%
“…The 382 use of a food atlas in Asia has previously been identified for the 383 education of people on portion sizes to try to reduce rates of 384 overweight and obesity (Thoradeniya et al, 2012). Although not 385 envisioned as an original function of the food atlas, the range of 386 portion sizes for traditional Middle Eastern and UAE foods, which 387 have not been quantified previously, may help educate people on 388 smaller portion sizes.…”
mentioning
confidence: 99%